Role of neutrophils in equine asthma. (24th May 2018) - Uberti, Benjamin; Morán, Gabriel
Abstract: Neutrophilic bronchiolitis is the primary lesion in asthma-affected horses. Neutrophils are key actors in host defense, migrating toward sites of inflammation and infection, where they act as early responder cells toward external insults. However, neutrophils can also mediate tissue damage in various non-infectious inflammatory processes. Within the airways, these cells likely contribute to bronchoconstriction, mucus hypersecretion, and pulmonary remodeling by releasing pro-inflammatory mediators, including the cytokines interleukin (IL)-8 and IL-17, neutrophil elastase, reactive oxygen species (ROS), and neutrophil extracellular traps (NETs). The mechanisms that regulate neutrophil functions in the tissues are complex and incompletely understood. Therefore, the inflammatory activity of neutrophils must be regulated with exquisite precision and timing, a task achieved through a complex network of mechanisms that regulates neutrophil survival. The discovery and development of compounds that can help regulate ROS, NET formation, cytokine release, and clearance would be highly beneficial in the design of therapies for this disease in horses. In this review, neutrophil functions during inflammation will be discussed followed by a discussion of their contribution to airway tissue injury in equine asthma.